Adaptasi Estetika Permainan Musik Barat pada Big Band Salamander - Oki Dirgualam; Dadang Suganda; Bucky Wikagoe; Kunto Sufianto (Jurnal Kajian Seni, 2021)
This article describes the adaptation of foreign culture in the form of jazz big band music by Salamander Big Band. Aesthetics is a study of the processes that occur in three basic elements, namely: aesthetic objects, aesthetic subjects, and aesthetic values related to aesthetic experiences, aesthetic properties, and attractive and unattractive parameters. The process of adapting the aesthetics of playing music is the process of adjusting the aesthetics of playing music carried out by an individual/community to cultural outcomes from outside the individual/community culture. This research uses qualitative approach method with descriptive analysis. Researchers describe the results of the research based on the results of observation, interview, and documental studies relating to players and experts in the field of big-band music. This paper presents the basic elements of western music aesthetics, especially big band jazz music and how Salamander Big Band can adapt and implement the aesthetic values of western jazz big band music in its music playing. Through a process of appreciation, habituation, additional insight into jazz music, continuous and consistent practice, Salamander Big Band members are able to adapt to cultures from outside of Indonesia’s popular music culture, that is playing American big band music with the correct aesthetic.Artikel ini menjelaskan tentang estetika permainan musik big band jazz yang diadaptasi oleh komunitas non-formal big band Salamander. Estetika merupakan kajian tentang proses yang terjadi pada tiga elemen dasar, yaitu: objek estetis, subjek estesis, dan nilai estesis yang terkait dengan pengalaman estesis, properti estesis, dan parameter kemenarikan maupun ketidakmenarikan. Proses adaptasi estetika permainan musik adalah proses penyesuaian estetika permainan musik  yang dilakukan oleh suatu individu/komunitas terhadap hasil budaya asing atau budaya baru. Tulisan  ini  menggunakan  pendekatan  kualitatif  dengan  metode  analisis  deskriptif. Tulisan ini menghadirkan elemen-elemen dasar dari estetika musik barat khususnya musik big band jazz serta bagaimana big band Salamander dapat mengadaptasi dan mengimplementasikan nilai-nilai estetika musik big band jazz barat dalam permainan musik yang dimainkan. Melalui proses adaptasi estetika dalam memainkan musik dengan benar dan sesuai, dapat menghasilkan produk musik yang lebih baik, mendekati estetika musik aslinya atau bahkan lebih baik dari versi aslinya.